Tracking Radiolabeled Endothelial Microvesicles Predicts Their Therapeutic Efficacy: A Proof-of-Concept Study in Peripheral Ischemia Mouse Model Using SPECT/CT Imaging - Romain Giraud; Anaïs Moyon; Stéphanie Simoncini; Anne-Claire Duchez; Vincent Nail; Corinne Chareyre; Ahlem Bouhlel; Laure Balasse; Samantha Fernandez; Loris Vallier; Guillaume Hache; Florence Sabatier; et al. (MDPI AG, 2022)
Microvesicles, so-called endothelial large extracellular vesicles (LEVs), are of great interest as biological markers and cell-free biotherapies in cardiovascular and oncologic diseases. However, their therapeutic perspectives remain limited due to the lack of reliable data regarding their systemic biodistribution after intravenous administration. Methods: Applied to a mouse model of peripheral ischemia, radiolabeled endothelial LEVs were tracked and their in vivo whole-body distribution was quantified by microSPECT/CT imaging. Hindlimb perfusion was followed by LASER Doppler and motility impairment function was evaluated up to day 28 post-ischemia. Results: Early and specific homing of LEVs to ischemic hind limbs was quantified on the day of ischemia and positively correlated with reperfusion intensity at a later stage on day 28 after ischemia, associated with an improved motility function. Conclusions: This concept is a major asset for investigating the biodistribution of LEVs issued from other cell types, including cancer, thus partly contributing to better knowledge and understanding of their fate after injection.